Half-metallic compensated ferrimagnetism with a tunable compensation point over a wide temperature range in the Mn-Fe-V-Al Heusler system - Stinshoff, Rolf; Fecher, Gerhard H.; Chadov, Stanislav; Nayak, Ajaya K.; Balke, Benjamin; Ouardi, Siham; Nakamura, Tetsuya; Felser, Claudia (AIP Advances, 2017)
The cubic Heusler compound Mn1.5FeV0.5Al with the L21 Heusler structure is the first fully compensated half-metallic ferrimagnet with 24 valence electrons. The ferrimagnetic state can be tuned by changing the composition such that the compensation point appears at finite temperatures ranging from 0 K up to 226 K, while retaining half-metallicity in the system. In this paper, the structural, magnetic and transport properties of the Mn-Fe-V-Al system are discussed. Magnetic reversal and a change of sign of the anomalous Hall effect were observed at the compensation point, which gives rise to a sublattice spin-crossing. These materials present new possibilities for potential spintronic devices because of their advantageous properties such as imperceptibility to external fields, lower power consumption and ultrafast switching in the THz region.
CRIS-Team Scopus Importer:2022-04-14